Exploring Partnership Governance in Global Health: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Solving the world's health challenges requires multidisciplinary collaborations that bring together the talents, experiences, resources, and ideas from multiple sectors. These collaborations in global health frequently occur through public2013private partnerships (PPPs) in which public and private parties share risks, responsibilities, and decision-making processes with the objective of collectively and more effectively addressing a common goal. However, these numerous stakeholders bring varying strengths and resources to global health partnerships, but they also bring their own organizational cultures, regulations, and expectations. Managing partnerships among them is complex and requires intentional and thoughtful governance. Over the last several decades, as the number of interested stakeholders, resources invested, and initiatives launched within the global health field has grown, effective governance of global health PPPs has become increasingly critical. To explore the role of governance in PPPs for global health, the Forum on Public2013Private Partnerships for Global Health and Safety convened a workshop. Participants explored best practices, common challenges, and lessons learned in the varying approaches to partnership governance. They also highlighted key issues in the governance of PPPs for global health with the goal of increasing their effectiveness in improving health outcomes. This publication summarizes the presentations and discussions from the workshop.

Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The potential misuse of advances in life sciences research is raising concerns about national security threats. Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies examines the U.S. strategy for reducing biosecurity risks in life sciences research and considers mechanisms that would allow researchers to manage the dissemination of the results of research while mitigating the potential for harm to national security.

Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.

Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Continuing advances in science and technology offer the promise of providing tools to meet global challenges in health, agriculture, the environment, and economic development; some of the benefits are already being realized. However, such advances have the potential to challenge the oversight systems for responsible conduct of life sciences research with dual use potential 2013 research that may have beneficial applications but that also could be misused to cause harm. Between June 10 and 13, 2018, more than 70 participants from 30 different countries and 5 international organizations took part in an international workshop, The Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight, to promote global dialogue and increased common understandings of the essential elements of governance for such research. Hosted by the Croatian Academy of Sciences and Arts in Zagreb, Croatia, the workshop was a collaboration among the InterAcademy Partnership, the Croatian Academy, the Croatian Society for Biosafety and Biosecurity, and the U.S. National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions from the workshop.

Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue - National Research Council (The National Academies Press, 2013)
Spurred on by new discoveries and rapid technological advances, the capacity for life science research is expanding across the globe2014and with it comes concerns about the unintended impacts of research on the physical and biological environment, human well-being, or the deliberate misuse of knowledge, tools, and techniques to cause harm. This report describes efforts to address dual use issues by developing institutes around the world that will help life sciences faculty learn to teach about the responsible conduct of science. Based on the successful National Academies Summer Institute for Undergraduate Biology Education and on previous NRC reports on effective methods for teaching about dual use issues, the report's authoring committee designed a general framework for the faculty institutes and chose the Middle East-North Africa (MENA) region to test a prototype faculty institute. In September 2012, the first Institute was held in Aqaba, Jordan, bringing together 28 participants from Algeria, Egypt, Jordan, Libya, and Yemen to engage with effective, evidence-based teaching methods, develop curricular materials for use in their own classrooms, and become community leaders on dual use and related topics. Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue offers insights from the institute that will help in the design and implementation of future programs in the MENA region, and in other parts of the world.

The Convergence of Infectious Diseases and Noncommunicable Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On June 11 and June 12, 2019, the National Academies convened a workshop to explore the growing understanding of how the interplay between humans and microbes affects host physiology and causes noncommunicable diseases. Discussions included an overview of colliding epidemics, emerging research on associations between infectious and noncommunicable diseases, risks posed by chronic diseases to the development and severity of infectious diseases, and the influence of the microbiome. Workshop participants also examined the challenges and opportunities of convergence, the integration of health care delivery models and interventions, potential approaches for research, policy, and practice in the immediate-term, and potential directions for the long-term. This publication summarizes the presentations and discussions from the workshop.